Jalanan Sebagai Ruang Deliberatif Kebijakan: Menguji Demonstrasi dalam Kerangka Jürgen Habermas - Ferrer, Vincensius Soma; Wulandari, Ayu (Journal of Government and Social Issues (JGSI), 2025)
Demonstrations are frequently characterized merely as protests against government policies or expressions of public dissent. However, viewed through the lens of Jürgen Habermas' deliberative democracy, they possess profound significance. Beyond mere confrontation, demonstrations serve as an arena for public communication where citizens interact, deliberate, and shape a collective political will. This study investigates the significant wave of protests across Indonesia in late 2025, demanding transparency and accountability in public budget management— specifically concerning the salary and allowance hikes for House of Representatives(DPR) members. Employing a qualitative case study design and critical discourse analysis, this research reveals that demonstrations function as informal deliberative spaces operating outside state institutions. Through spontaneous communication, participants not only articulate political demands but also construct a shared understanding of public exigencies, particularly fiscal justice and financial accountability. This phenomenon illustrates that deliberative practices are not confined to formal forums; they can emerge organically on the streets, transforming citizens into active subjects of policy discourse. Consequently, this study validates demonstrations as a legitimate component of Indonesia's deliberative democracy and contributes to the conceptual strengthening of participatory and responsive public governance.